Pembatalan Pernikahan (Fasakh Nikah) Dalam Berbagai Legislasi - Slamet Arofik (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
In a marriage, sometimes something happens that causes the marriage to no longer be continued or the marriage is cancelled. fashak nikah is one part of the occurrence of marriage annulment, when fashak occurs, of course there are characteristics or signs why, fashak nikah can occur. These signs are more to the pillars and conditions of marriage determined by the Shari'ah. fashak is a termination of marital relations from the court that is reported by one party, either from the wife or from another party, who knows there is a discrepancy with the law of marriage which makes them unable to achieve the goals of the marriage.